KAJIAN PASIR SILIKA SEBAGAI AGREGAT HALUS PADA CAMPURAN ASPHALT CONCRETE WEARING COURSE (AC – WC) BERDASARKAN UJI MARSHALL - Nofrianto, Hendri; Dwi Astika, Septiana (ITP Press, 2023)
Aggregate is the main component in the formation of asphalt mixtures, in which the weight of aggregate ranges from 90%-95% of the total weight of the asphalt mixture. Usually, the aggregate used is obtained directly from nature and is a non-renewable material so that its availability continues to decrease. One of the alternative aggregates utilized is silica sand which is a waste originating from Karang Putih Hill, Padang City, West Sumatra, it is hoped that this silica sand waste can be used as an alternative aggregate in asphalt mixtures on flexible pavements. This research aims to analyze the characteristics of asphalt mixtures using silica sand as fine aggregate and further review the effect of water on the durability of the mixture through immersion tests with variations of immersion of 0 hours, 24 hours, 48 hours, 72 hours and 96 hours based on marshall testing. The results of this study indicate that silica sand can be used as an alternative aggregate in road pavements, this can be concluded based on the values of the marshall parameters of silica sand within the specifications used, the use of silica sand in the Asphalt Concrete - Wearing Course (AC-WC) mixture has an optimum asphalt content value of 5.7%. Durability of asphalt mixtures with silica sand seen from the results of the immersion test decreases as the immersion duration increases, the Residual Strength Index (IKS) value meets the requirements of Bina Marga 2018 Revision 2 specifications up to a 24-hour immersion duration with a value of 93.94%.